New Approach to the Development of Gas Hydrate Accumulations Located at the Bottom of the Seas and Oceans - Samandar wazeri (Swara Patra, 2020)
Nowadays fundamental scientific researches and practical works are carried out worldwide to identify and use alternative sources and resources of energy carriers in place of oil and gas. In the world practice, to date, there are no technologies and technology for the development of gas hydrate accumulations and gas hydrate deposits located at the bottom of the seas and oceans. In this article, some methods of possible drilling of conditional wells are being discussed, that is, the creation of gas-hydrodynamic channels for lifting gas through the water column and decomposition of gas hydrates inside gas-hydrate clusters-strata. The possibility of creating double-barrel horizontal wells for supplying the heat carrier and inhibitor to the bottom hole zone for fracturing the gas hydrate and producing gas by a single well is considered.